1992
DOI: 10.1093/ajcn/55.6.1161
|View full text |Cite
|
Sign up to set email alerts
|

Daily magnesium supplements improve glucose handling in elderly subjects

Abstract: We demonstrated similar plasma concentrations and urinary losses but lower erythrocyte magnesium concentrations (2.18 +/- 0.04 vs 1.86 +/- 0.03 mmol/L, P less than 0.01) in twelve aged (77.8 +/- 2.1 y) vs 25 young (36.1 +/- 0.4 y), nonobese subjects. Subsequently, aged subjects were enrolled in a double-blind, randomized, crossover study in which placebo (for 4 wk) and chronic magnesium administration (CMA) (4.5 g/d for 4 wk) were provided. At the end of each treatment period an intravenous glucose tolerance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(116 citation statements)
references
References 19 publications
1
113
0
2
Order By: Relevance
“…22 Chronic magnesium supplementation was found to improve insulin response to glucose load and glucose disposal rate in hyperinsulinemic euglycemic clamp studies. 7,9 In a study by Wang et al, patients with T2DM who were in the upper quartile of magnesium intake (quantified through food questionnaires) had a mean HOMA-IR of 3 (a value of >3.6 interpreted as insulin resistant). 23 Multiple prospective cohort studies have tested the efficacy of magnesium supplementation on glycemic control, with conflicting results.…”
Section: Magnesium Intake Risk Of Diabetes and Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…22 Chronic magnesium supplementation was found to improve insulin response to glucose load and glucose disposal rate in hyperinsulinemic euglycemic clamp studies. 7,9 In a study by Wang et al, patients with T2DM who were in the upper quartile of magnesium intake (quantified through food questionnaires) had a mean HOMA-IR of 3 (a value of >3.6 interpreted as insulin resistant). 23 Multiple prospective cohort studies have tested the efficacy of magnesium supplementation on glycemic control, with conflicting results.…”
Section: Magnesium Intake Risk Of Diabetes and Insulin Resistancementioning
confidence: 99%
“…3,5,6 Oral supplementation or intravenous infusion of magnesium in diabetic patients increases acute insulin response and glucose disposal rate, and decreases insulin resistance. [7][8][9][10] Because of these findings, magnesium has been suggested as a possible treatment for diabetes. Several randomized controlled trials on the effect of magnesium supplementation on glycemic control in diabetes have conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Although many authors have suggested that diabetes per se may induce hypomagnesemia, others have reported that higher Mg intake may confer a lower risk for type 2 diabetes (20 -23). It is interesting that the induction of Mg deficiency has been shown to reduce insulin sensitivity in individuals without diabetes, whereas Mg supplementation during a 4-wk period has been shown to improve glucose handling in elderly individuals without diabetes (18,24). In patients with type 2 diabetes, oral Mg supplementation during a 16-wk period was suggested to improve insulin sensitivity and metabolic control (25).…”
Section: Hypomagnesemia and Diabetes: Cause And Effectmentioning
confidence: 99%
“…Refining wheat to white flour results in a 33% retention of magnesium in Australian flour compared with a 15% retention in the United States (Schroeder, 1971;Mugford, 1983;United States Department of Agriculture, 2003). Low blood levels of magnesium are associated with impaired insulin secretion and function, poor glycaemic control, and diabetic complications (Paolisso et al, 1992;White & Campbell, 1993;Rosolova et al, 1997). Urinary excretion of magnesium is raised in people with diabetes and it has been suggested that hypomagnesaemia is a possible consequence of diabetes (Khan et al, 1999).…”
Section: Nutrient Retentionmentioning
confidence: 99%